Cedecea sp. Isolated from a canine pyometra. Case communication (Veterinary Science, 2017)
Gender Cedecea belongs to the Enterobacteriaceae family and comprises Gram negative, facultative anaerobic, non spore-forming bacilli. Clinical importance of this genre has not been elucidated. There are few clinical cases reported in humans and animals. This article aims to describe the isolation of a strain of Cedecea sp from a sample of pyometra in a canine with hemangiosarcoma of older age
Keywords: Cedecea; pyometra; canine